Investigation of the Hottel–Whillier–Bliss Model Applied for an Evacuated Tube Solar Collector - Márton Rátkai; Gábor Géczi; László Székely (Eng)
The goal of this research is to examine the applicability of the Hottel–Whillier–Bliss model, developed for flat-plate collectors, to evacuated tube solar collectors. During this study, the model is applied to an evacuated tube collector, and then the identification and validation of the model are made with the help of measurements performed on the collector. This research also includes the application, identification and validation of the energy balance model for the investigated solar collector. This model works for both flat-plate and evacuated tube collectors. The results obtained with the two different models are then compared. By comparing the modelled results with the measured values, the accuracy and applicability of the models can be determined. Based on the results, the Hottel–Whillier–Bliss model works excellently with evacuated tube solar collectors for predicting the outlet temperature of the medium from the solar collector. It is important to note that the identification gives negative heat transfer parameter values. According to the validation, the average absolute error is 0.8 °C, and the average relative error is 1%. For the energy balance model, these values are 0.87 °C and 1.1% respectively, indicating that the accuracy of the Hottel–Whillier–Bliss model is very similar, and even slightly higher. Additionally, the research provides further proof of the applicability of the energy balance model to evacuated tube collectors.